Bacterial Meningitis in Neonates: A Multicenter Descriptive Study in the City of Medellín, Colombia (2023)
ABSTRACT: Introduction: Bacterial meningitis is a severe infection requiring early empirical therapeutic intervention. In Colombia, there is limited information regarding this disease in the neonatal stage, necessitating up-to-date data to guide timely antibiotic therapy. Objective: To describe the clinical, microbiological, and epidemiological characteristics of neonatal bacterial meningitis in three hospital centers in the city of Medellín during the years 2010 to 2019. Methods: A descriptive study was conducted using electronic medical records of newborns treated in three hospitals in Medellín from 2010 to 2019. Clinical records with a discharge diagnosis of bacterial meningitis and corresponding microbiological isolation were reviewed. Data were extracted from SAP® and Servinte Clinical Suite Enterprise® and recorded in a Google® spreadsheet. Results: A total of 125 records with a diagnosis of neonatal meningitis were reviewed with only 42 cases meeting microbiological isolation criteria.The mean gestational age was 35 weeks, and the most frequentlyisolated pathogens were Escherichia coli (40.5%) and Streptococcus agalactiae (40.5%). In 71.4% of cases, the meningitis was classified as late-onset according to age. Primary symptoms included irritability (56.1%) and fever (48.8%). Conclusions: The most common causative agents identified in this population were S. agalactiae and E. coli. Principal symptoms were irritability and fever. A significant proportion of neonates did not present suggestive symptoms of central nervous system infection. Additionally, prematurity was predominant in the studied population.